Risk and return relationship in Malaysian finance sector: empirical evidence from capm - Wong, Wang Ling (Universiti Malaysia Sarawak (UNIMAS), 2012)
ThiS study examines the applicability of Capital Assets Pricing Model (CAPM) in explaining the risk and return relationship of the Malaysian stock market. The analysis of monthly stock market closing indexes from January 2005 to December 2010 using linear regression method was carried out on the standard CAPM model with constant be0 The results revealed that the standard CAPM model is statistically significant. Test results indicate that this model demonstrated excess return of the stock is depending on systematic market risk. This study examined a conditional relationship between risk and returns during market's up and down. The study also found that linear regression indicates moderate explanatory power of beta for the excess return.